Making sense of being and becoming Filipinos an indigenous psychology perspective. [article]. - Yacat, Jay A. .
This qualitative study explored how 36 undergraduate students from the University of the Philippines who were born, raised and currently residing in the Philippines make sense of their 'pagka-Pilipino' (being Filipinos). Using the method of ginabayang talakayan(indigenous facilitated discussions), it was found that notions of 'being Filipino' were shaped by any of three factors: a sense of shared orighins(pinagmulan); growing up in a similar cultural milieu(kinalakhan) and a shared consciousness(kamalayan). This may suggest uniformity in the participants' definitions of 'who the Filipino is' but analysis reveals that different people and groups tends to place different emphases on the three factors in their own attempts to come to terms with their identities as Filipinos. Hence, 'Filipino' and 'being a Filipino' may evoke different meanings among different people. -- (from the author)